An Analysis Of Moral Values In “Up’’ Movie - Windriani W (Jurnal Ilmiah Mahasiswa Pendidikan [JIMEDU], 2021)
This research discusses about the moral values of the characters in the "Up" movie. The purpose of this research is to identify the types of moral values in the "Up" movie and to determine the types of moral values that occur in the "Up" movie. The research was conducted by applying descriptive qualitative research. The data sources are taken from the entire "Up" movie and the transcript of the "Up" movie which focuses on the use of moral values and types of moral values. They consist of 100 pages as data. The findings of this research, in the "Up" movie, found some moral values that occur. The types of moral values in the movie "Up" are; never give up, altruism, love and loyalty, respect, help each other, courage and self-discipline. From this research, the researcher hopes that after reading this research, the reader understand about moral values. Keywords: Movie, Moral Value.